COMPATABILITY BETWEEN INTERNATIONAL HUMANITARIAN LAW AND ISLAMIC LAW OR WAR (JIHAD) - Faiz Bakhsh (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2019)
This study investigates the matter of the compatibility between International Humanitarian Law and Islamic concept of Jihad. The proponents of the theory of the acceptability of International Humanitarian Law in an Islamic context have been presenting the similarities between International Humanitarian Law and Islam. The opponents have been trying to point out the differences between International Humanitarian Law and Islam, especially on the violent concept of Jihad. This study looks at the theories of the existence or non-existence of a fundamental conflict between International Humanitarian Law and Islam by analysing the views of different schools of thoughts and rules of International Humanitarian Law in the context of Islamic Law of War (Jihad). The lack of the availability of a satisfactory study on the matter provides justification for the present study that aims to address the gap by making an important contribution to the knowledge in this area. The analyses of the data lead us to the point where the relationship between International Humanitarian Law and Islam becomes clear and an assessment is made about the compatibility of International Humanitarian Law with Islam, on the Islamic concept of Jihad. Abstrak: Studi ini menganalisis masalah kompatibilitas Hukum Humaniter Internasional dan konsep Islam tentang Jihad. Para pendukung teori Hukum Humaniter Internasional dalam konteks Islam telah menyampaikan persamaan antara Hukum Humaniter Internasional dan Islam. Sementara itu, para penentang hukum ini juga telah berusaha menunjukkan perbedaan antara Hukum Humaniter Internasional dan Islam, terutama pada konsep kekerasan Jihad. Penelitian ini mengkaji teori-teori tentang ada atau tidaknya konflik mendasar antara Hukum Humaniter Internasional dan Islam dengan menganalisis pandangan berbagai mazhab dan aturan Hukum Humaniter Internasional dalam konteks Hukum jihad dalam Islam. Terbatasnya penelitian yang baik berkaitan dengan masalah ini memberikan justifikasi untuk penelitian ini, yang bertujuan untuk menutupi kesenjangan dengan memberikan kontribusi penting untuk pengetahuan di bidang terkait. Analisis data mampu menjelaskan hubungan antara Hukum Humaniter Internasional dan Islam dan menilai kompatibilitas antara Hukum Humaniter Internasional dan Islam, pada konsep Islam tentang Jihad. Kata kunci: Hukum Humaniter Internasional, Hukum Perang Islam, Kompatibilitas